2016
DOI: 10.15252/embr.201642671
|View full text |Cite
|
Sign up to set email alerts
|

Structural role of the T94I rhodopsin mutation in congenital stationary night blindness

Abstract: Congenital stationary night blindness (CSNB) is an inherited and non-progressive retinal dysfunction. Here, we present the crystal structure of CSNB-causing T94I2.61 rhodopsin in the active conformation at 2.3 Å resolution. The introduced hydrophobic side chain prolongs the lifetime of the G protein activating metarhodopsin-II state by establishing a direct van der Waals contact with K296, the site of retinal attachment. This is in stark contrast to the light-activated state of the CSNB-causing G90D2.57 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 51 publications
4
41
0
Order By: Relevance
“…Rhodopsin is the first GPCR that had structures determined in the inactive and active states with and without agonist ( 9 ) and in an arrestin-bound state ( 5 ). In addition, rhodopsin is the only GPCR for which structures of human disease mutants have been solved ( 10 , 11 ). Comparisons of these structures revealed that rhodopsin activation results in the opening of a cleft on the cytoplasmic side of the receptor and the formation of a binding cavity for the C-terminal domain (α5) of G t .…”
Section: Introductionmentioning
confidence: 99%
“…Rhodopsin is the first GPCR that had structures determined in the inactive and active states with and without agonist ( 9 ) and in an arrestin-bound state ( 5 ). In addition, rhodopsin is the only GPCR for which structures of human disease mutants have been solved ( 10 , 11 ). Comparisons of these structures revealed that rhodopsin activation results in the opening of a cleft on the cytoplasmic side of the receptor and the formation of a binding cavity for the C-terminal domain (α5) of G t .…”
Section: Introductionmentioning
confidence: 99%
“…The protocol integrates a set of methods to qualitatively evaluate the impact of detergent and deglycosylation during preparation of the rhodopsin-mini-G o complex. Rhodopsin at inactive state and light-activated state bound with and without the transducin peptide has been crystallized when purified in the detergents octyl glucoside (C8G) 20,21,22 and C9G 23,24 . As the rhodopsin-mini-G o complex purified in C8G and C9G did not yield crystals (data not shown), we then explored a wider range of other detergents using the strategy described (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…4-7 were prepared using PYMOL (The PyMOL Molecular Graphics System, Version 2.0 Schrödinger, LLC.) from the coordinates of inactive (PDB ID: 1GZM 17 ) and active (PDB ID: 2X72 32 ) bovine rhodopsin, of the adenosine A2A receptor solved by serial millisecond crystallography at room-temperature (PDB ID: 5NM4 22 ), of the T94I rhodopsin mutant (5DYS 19 ), and of bacteriorhodopsin in the ground state obtained with serial femtosecond crystallography (5J7A 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15] These water molecules have several roles including an essential function for the changes that occur aer activation. Specically, three major roles can be assigned to water molecules: (1) they can be important components of hydrogen bond networks that stabilise the overall structures of inactive and active states 11,[16][17][18][19] (Fig. 2 and 3); (2) they can provide a local hydrophilic environment for polar ligands (Fig.…”
Section: Introductionmentioning
confidence: 99%